Effect of Aluminium Loading on SiO2/Al2O3-NiMo Catalysts Synthesized via KHP-template for Crude Palm Oil Hydrocracking - Hasanudin Hasanudin; Mhika Nakashima; Wan Ryan Asri; Novia Novia; Fitri Hadiah; Roni Maryana; Muhammad Al Muttaqii; Nino Rinaldi (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
The present study evaluates the catalytic activity of SiO2/Al2O3‒x and SiO2/Al2O3‒x‒NiMo (where x = 5, 10, 25 g of aluminium weight) synthesized using a potassium hydrogen phthalate (KHP) template-assisted route for the hydrocracking of crude palm oil (CPO) into biofuels. Increasing Al weight modified acidity, porosity, and NiMo dispersion, leading to distinct catalytic behavior. The optimal SiO2/Al2O3‒x‒NiMo catalyst (10 g Al) achieved ~94% conversion, dominated by jet fuel-range hydrocarbons (C10-C14) through synergistic hydrodeoxygenation and acid-catalyzed cracking-isomerization pathway. The enhanced performance originates from the balance between acidity and metal dispersion, highlighting that both template selection and Al loading govern the design of efficient SiO2/Al2O3‒NiMo catalysts for biofuel production. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).